Lies, lies, lies : a novel - Parks, Adele (Mira, 2024)
After years together, the arrival of longed-for daughter Millie sealed everything in place. A happy little family of three. And so what if Simon drinks a bit too much sometimes--Daisy's used to it, she knows he's letting off steam. Until one night at a party things spiral horribly out of control. And that happy little family of three will never be the same again. --